Knowledge of teachers and staff about first aid in a school setting: an almost experimental survey (Research, Society and Development, 2020)
Objective: to assess the knowledge of teachers and employees of a primary and secondary school, before and after an educational intervention on first aid. Method: quasi-experimental research with a single group, before and after type. The data were collected through a questionnaire, applied before and after the intervention. The sample consisted of 38 teachers and employees. Results: the average number of correct answers about knowledge in first aid increased from 11.13 to 19.45. There was a significant improvement in the participants' knowledge regarding questions about breathing (p=0.001; p=0.004), cardiorespiratory arrest (p=